Crystal structure of besifloxacin hydrochloride, C19H22ClFN3O3Cl. Issue 1 (March 2023) - Kaduk, James A.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of besifloxacin hydrochloride has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional theory techniques. Besifloxacin hydrochloride crystallizes in space group P 1 (#1) with a = 5.36596(8), b = 10.3234(4), c = 17.9673(14) Å, α = 98.122(5), β = 92.9395(9), γ = 96.1135(3)°, V = 977.483(13) Å 3, and Z = 2. The crystal structure is approximately centrosymmetric. Strong N–H⋯Cl hydrogen bonds form a corrugated ladder-like chain along the a -axis. The carboxylic acid group in each independent cation acts as the donor in a strong intramolecular O–H⋯O hydrogen bond to an adjacent carbonyl group. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).